More than iso/anisohydry: Hydroscapes integrate plant water use and drought tolerance traits in 10 eucalypt species from contrasting climates - Li, Ximeng; Blackman, Chris J.; Peters, Jennifer M. R.; Choat, Brendan; Rymer, Paul D.; Medlyn, Belinda E.; Tissue, David T. (Functional ecology, 2019)
The iso/anisohydric continuum describes how plants regulate leaf water potential and is commonly used to classify species drought response strategies. However, drought response strategies comprise more than just this continuum, incorporating a suite of stomatal and hydraulic traits. Using a common garden experiment, we compared and contrasted four metrics commonly used to describe water use strategy during drought in 10 eucalyptus species comprising four major ecosystems in eastern Australia. We examined the degree to which these metrics were aligned with key stomatal and hydraulic traits related to plant water use and drought tolerance. Species rankings of water use strategy were inconsistent across four metrics. A newer metric (Hydroscape) was strongly linked to various plant traits, including the leaf turgor loss (TLP), water potential at stomatal closure (Pgs90), leaf and stem hydraulic vulnerability to embolism (PL50 and Px50), safety margin of hydraulic segmentation (HSMHS), maximum stomatal conductance (gsmax) and Huber value (HV). In addition, Hydroscape was correlated with climatic variables representing the water availability at the seed source site. Along the continuum of water regulation strategy, species with narrow Hydroscapes tended to occupy mesic regions and exhibit high TLP, PL50 and Px50 values and narrow HSMHS. High gsmax recorded in species with broad hydroscapes was also associated with high HV. Despite a fourfold difference in Hydroscape area, all species closed their stomata prior to the onset of hydraulic dysfunction, suggesting a common stomatal response across species that minimizes embolism risk during drought. Hydroscape area is useful in bridging stomatal regulation, hydraulic architecture and species drought tolerance, thus providing insight into species water use strategies. A plain language summary is available for this article. Plain Language Summary